KARAKTERISTIK CAMPURAN ASPHALT CONCRETE–WEARING COURSE (AC-WC) DENGAN PENGGUNAAN ABU VULKANIK DAN ABU BATU SEBAGAI FILLER - Hadi Ali (UNIVERSITAS LAMPUNG, 2011)
KARAKTERISTIK CAMPURAN ASPHALT CONCRETE–WEARING COURSE (AC-WC) DENGAN PENGGUNAAN ABU VULKANIK DAN ABU BATU SEBAGAI FILLERHadi AliAbstractAsphalt concrete layer construction casing layer perkerasan road that has structural value. one of the asphalt concrete layer kind asphalt concrete - wearing course (ac-wc) as top-ranking layer in perkerasan bent. composers principal materials aggregate and asphalt, belong kind filler in its use. in this watchfulness is kind filler that is used vulcanic ash and stone ash as the standard. Before done testing marshall in mixture, done testing towards materials that used it. specific gravity testing result in filler vulcanic ash 2,819 gr/cm3 and 2,351 gr/cm3 for stone ash, while materials escapes 75 microns in filler vulcanic ash and stone ash is taken 100%. plan asphalt degree that used good in mixture with filler vulcanic ash also stone ash pb = 5,5% with plan asphalt degree distance 4,5%; 5%; 5,5%; 6% and 6,5%. After done test marshall with plan asphalt degree, entire characters marshall in standard test 2x75 collision has fulfilled spesification menyyaratkan. result that got density and stability marshall with vulcanic ash has higher value from in mixture with stone ash. in entire asphalt degree distances, value flow mixture with filler higher stone ash from in mixture with filler vulcanic ash. highest value in stone ash asbig as 4,667 mm, while vulcanic ash as big as 4,2667 mm. marshall quottient for both types of filler, bottommost value happens in highest asphalt degree (6,5 %) that is as big as 217,19407 kg/mm to filler stone ash and 239,5274 kg/mm to filler vulcanic ash. filler vulcanic ash has value vfa higher from in stone ash, but value vma lower. while air hole value in mixture (vim), filler higher stone ash from in vulcanic ashKeyword : stone ash, vulcanic ash.